Advances in accounting education teaching and curriculum innovations. Vol. 4 - Ketz, J. Edward; Schwartz, Bill N. (Emerald, 2002)
A refereed, academic research annual whose purpose is to meet the needs of individuals interested in ways to improve their classroom instruction. Articles may be either empirical or non-empirical. They emphasize pedagogy, for example, explaining how teaching methods or curricula/programmes can be improved.
Keywords: Business & Economics -- Accounting -- General.; Science -- History.; Teaching skills & techniques.; Accounting.; Accounting -- Study and teaching.; elektronické knihy; electronic books